MLPA in the initial genetic screening of patients with acute myeloid leukemia - Yahya Dinnar; Hachmeriyan Mari; Ruseva Tsanka; Chervenkov Trifon; Micheva Ilina (Sciendo, 2024)
This study aimed to assess the effectiveness of multiplex ligase-dependent probe amplification (MLPA) in the initial genetic screening of patients with acute myeloid leukemia (AML) since current risk stratification and clinical management depend on molecular-genetic markers.